Reconstructing the Epistemology of Legal Education: From Positivism to Humanistic Paradigms - Ash-shidiqqi, Ellectrananda Anugerah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The epistemological foundation of legal education has long been dominated by positivistic thought, strongly influenced by thinkers such as Hans Kelsen and H.L.A. Hart, emphasizing legal certainty, formal logic, and the mechanical application of rules. While this paradigm has been effective in cultivating technical competence and doctrinal precision, it has simultaneously marginalized the moral, philosophical, and social dimensions of law as a living and dynamic system. Consequently, legal education often produces graduates who are procedurally skilled yet insufficiently responsive to substantive justice and humanitarian concerns. This study aims to reconstruct the epistemology of legal education by shifting from a rigid positivist framework toward a humanistic paradigm that integrates ethical consciousness, critical reflection, and social responsibility. Using a normative-philosophical approach supported by conceptual analysis of classical and contemporary legal theories, including critiques advanced by Ronald Dworkin and Jürgen Habermas, this research examines how the dominance of positivism has constrained legal reasoning and distanced law from its emancipatory purpose. The findings reveal that formalistic and text-centered approaches in legal education limit students’ capacity to engage with justice in its broader social and moral contexts. Therefore, this study proposes an epistemic reconstruction centered on dialogical learning, intersubjective understanding, and contextual engagement with social realities. By situating law within ethical, cultural, and societal frameworks, this humanistic model envisions legal education not merely as a mechanism for producing technically proficient jurists, but as a transformative process that nurtures reflective, compassionate, and socially responsible legal thinkers committed to the realization of substantive justice.